2016
DOI: 10.1002/etc.3376
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of potential mechanisms of atrazine‐induced reproductive impairment in fathead minnow (Pimephales promelas) and Japanese medaka (Oryzias latipes)

Abstract: Atrazine has been implicated in reproductive dysfunction of exposed organisms, and previous studies documented decreased egg production in Japanese medaka (Oryzias latipes) and fathead minnows (Pimephales promelas) during 30-d to 38-d exposures to 0.5 µg/L, 5 µg/L, and 50 µg/L atrazine. The authors evaluated possible mechanisms underlying the reduction in egg production. Gene expression in steroidogenesis pathways and the hypothalamus-pituitary-gonad axis of male and female fish was measured. Atrazine did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 41 publications
2
24
2
Order By: Relevance
“…b Only one sample analyzed. However, the study by Richter et al [23] did not observe the same alterations in hepatic expression of ERa as the present study. Samples were taken from stock replacement water prepared for both fish and frogs on days 0 and 6 (n ¼ 2).…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…b Only one sample analyzed. However, the study by Richter et al [23] did not observe the same alterations in hepatic expression of ERa as the present study. Samples were taken from stock replacement water prepared for both fish and frogs on days 0 and 6 (n ¼ 2).…”
Section: Discussioncontrasting
confidence: 69%
“…Values represent the mean (AE standard error of the mean). Following a 30-d exposure to atrazine at the same nominal concentrations as the present study, female fathead minnows experienced down-regulations of genes involved in gonadal steroidogenesis and luteinizing hormone signaling that were also associated with reduced egg production [23]. n.d. ¼ not detected.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Although there was a statistically significant increase in expression of vtg-II in males exposed to 5.5 mg/L, the relatively large degree of variability within the treatment group (fold change of 6.9 AE 3.8), particularly in 2 fish in replicate D demonstrating fold changes of 16.2 and 25.51 versus 0.31 to 7.10 for the other 8 male fish in this treatment replicate, and the lack of concurrent effects on the other measured reproductive endpoints suggested that the upregulation of the gene did not translate to significant effects in reproductive fitness. Richter et al [32] also reported a lack of dose-dependent expression of hepatic vitellogenin (vtg-I) in medaka exposed to up to 50 mg/L for 14 or 38 d and noted that this was in agreement with other characterizations of effects of atrazine in fish and amphibians. Likewise, Span o et al [27] reported that atrazine at concentrations up to 1000 mg/L had no effect on plasma vitellogenin levels in goldfish, and the review by Van Der Kraak et al [9] concluded that the weight of evidence suggested that atrazine exposure had no effects on vitellogenin in fish.…”
Section: Reproduction and Secondary Sex Characteristicssupporting
confidence: 67%